IMPORTANCE OF ELBOW FLEXOR MUSCLE STRENGTH AND ENDURANCE IN SPORTS CLIMBING - Michail Michailov; Stanislava Lambreva; Diana Deneva; Hristo Andonov (Scientific Publishing House. NSA Press, 2017)
The muscles that exert most during sport climbing are the finger flexors followed by elbow flexors (EF). Nevertheless, climbers' EF strength and endurance have not been tested in an isolated manner and EF endurance has not been assessed at different relative intensities. Purpose: To determine the importance of EF maximal strength and endurance in sports climbing. Methods: Nine male sports climbers and a control group of seven male sports students performed an EF maximal strength (MS) test and four EF endurance tests representing isometric muscle contractions at 90%, 70%, 50% and 30% of the maximal voluntary contraction (MVC). Results: Sports climbers sustained longer than the controls at 70 % (39±11 versus 28±7 s; p=0.044, η2=0.259) and 50%MVC (57±10 versus 48±6 s; p=0.050, η2 =0.248). The highest effect size was estimated for the force-time integral related to body mass at 70% MVC (107±27 versus 75±18 N.s/kg; p=0.018, η2 = 0.338). The two groups did not differ in MS (313±52 versus 338±55 N; p=0.372) or MS related to body mass (4.6±0.6 versus 4.2±0.8 N/kg; p=0.623). Climbing ability significantly correlated only with MS related to body mass. The relationship between MS related to body mass and on sight ability was strong (r=0.806, p=0.016). Conclusion: EF strength and endurance appear to be key performance factors in sports climbing. Sports climbing demands a high level of EF endurance during muscle contractions of high intensity. An excessive increase of EF endurance would not necessary lead to a significant improvement in climbing ability. However, higher climbing ability demands increased EF maximal strength.